Comparison of Disclosure Level among Islamic Banks and Its Effect on Performance - Nadia Hanif; Noman Arshed (Islamic Banking and Finance Review, 2016)
Revealing accurate and complete information of the business is the prime focus of Islamic finance as it proposes to avoidance any sort of Gharar (uncertainty). Lack of disclosure could lead to exploitation of the information by few members in the market at the expense of others. The difference between Islamic Bank and Conventional Bank is that Islamic bank takes disclosure of governance status as a religious obligation as compared to disclosure of conventional banks based upon legal obligation of the country. Similarly, Islamic banks put efforts in disclosing information of Shari’ah governance and social responsibility as per religious obligation as compared to voluntary disclosure by conventional banks. This study is built on the idea that if Islamic Bank considers Shari’ah disclosure and social responsibility as voluntary disclosure then it is expected that there will be a significant difference between all present Islamic banks. Lastly, this study has generated an overall disclosure index using principal factor analysis and evaluated its impact on the performance of the banks to reveal that disclosure entails positive impact on performance.